Transition pathways for Malaysian paddy farmers to sustainable agricultural practices: An integrated exhibiting tactics to adopt Green fertilizer - Adnan, N. (Elsevier Ltd, 2020)
Sustainable agriculture mainly depends on the efforts and abilities of farmers that depend on the rational decisions and actions taken by them with the help of their practical knowledge and information. Recent advances in the field of nanomaterials such as graphene possess the significant potential benefits for both agriculture and the environment. Therefore, for promoting sustainable agriculture farmer's outlook needs to be more towards the social approach rather a technocratic approach. The purpose of this research is to examine paddy grower's perception of productive paddy farming in peninsular Malaysia. So, for this study, a sample of 74 paddy farmers had adopted to have their insights and opinions about predefined sustainable practices of farming. Altogether 86 items were factor analysed and eventually, there are five main factors, policy, namely, environmental, economic and social and communication which was acknowledged to construct a perception of sustainability by considering the sustainable agricultural practices among Malaysian paddy farmers insights were characterized mainly into three groups like low, medium and high-level insights. This was considered as the dependent variable of the ordered research model, whereas socioeconomic characteristics and communication behaviour variables were used as a variable. The results of this research model reflected that communication channels, environmental factors, socio-psychological, socioeconomic aspect, and innovation attributes education level, age, participation in farming events and productive using of knowledge the perception of sustainable farming lead to the adoption of GFT among Malaysian paddy farmers. The government should be more focused towards policy linked with the issues like illegal paddy entry, plus social elements such as increasing the level of socialization and communication between stakeholders, researchers, a scientist in the region and giving out some special programs related to farming. Â© 2019